Self-care practices and influencing factors among type 2 diabetes mellitus patients: A hospital-based cross-sectional study - Nirmal Jyoti Jyotsana; Niraj Pandit; Salil Sharma; Laxman Kumar (Clinical Epidemiology and Global Health)
Background: Diabetes mellitus (DM) is a widespread non-communicable disease in India that significantly affects the healthcare system owing to its acute and chronic complications. The traditional approach to diabetes care has focused on medical professionals, but recent research has indicated that self-care among patients is crucial. Effective self-care practices can enhance the quality of life of T2DM patients. This study aimed to evaluate self-care practices among T2DM patients at a sub-district hospital in Gujarat State, India. Methods: This cross-sectional study included 93 T2DM patients. Self-care activities were assessed using the Summary of Diabetes Self-Care Activities (SDSCA) scale. Descriptive statistics and comparative analyses were performed. Results: The majority of the participants were male (55.9 %) and over 60 years of age (67.7 %). Participants demonstrated high adherence to medication regimens (mean score = 6.66 ± 0.86). However, adherence to other self-care practices was significantly lower; only 11.8 % reported good dietary behavior, 55.91 % engaged in regular exercise, and 50.5 % performed regular foot care. While 83.8 % reported good monitoring behavior, this contradicts the low adherence to blood glucose testing (mean score = 0.38 ± 0.59). Participants aged <60 years tended to report slightly better adherence to blood glucose testing than those aged ≥60 years. Conclusion: This study revealed a gap in self-care practices among T2DM patients in Gujarat. Despite good medication adherence, the patients demonstrated poor adherence to diet, exercise, and foot care. These findings emphasize the importance of customized interventions to improve self-management education and support, particularly for older adults.